The Problematic Use of Ḍa’īf Al-Ḥadīth: A Study of Ibn Ḥajar al-Asqalānī’s Thoughts and Practices in Bulūgh al-Marām: Problematika Penggunaan Hadis Dha'īf : Studi tentang Pemikiran dan Praktik Ibn Hajar Al-Asqalani dalam Bulūgh al-Marām - Wafa Fauziyyah; Hilda Yessy Diah Pernanda (Jurnal Living Hadis, 2024)
Problems arising within society are often rooted in the uncritical acceptance and application of dha’if (weak) traditions, particularly in matters of worship. Interestingly, Ibn Ḥajar al-’Asqalānī, a renowned hadith scholar, extensively quotes various hadiths, including dha’if ones, in his seminal work Bulūgh al-Marām, a book focused on Islamic legal rulings that ideally should be based on authentic, hadith ṣaḥiḥ or ḥasan. This study examines Ibn Ḥajar’s perspective on utilizing hadith dha’if, guided by two central research questions. First, what are Ibn Hajar’s view and considerations in incorporating dha’if hadiths into Bulūgh al-Marām? Second, what is the position and validity of dha’if traditions within the broader discourse of Islamic jurisprudence? The study employs a descriptive-analytical method grounded in a literature review to address these questions. The findings reveal that Ibn Ḥajar permits the use of hadiths dha’if under specific conditions; the weakness must not be severe, the narration should align with established principles or stronger evidence, and it must not be definitively attributed to the Prophet. In Bulūgh al-Marām, hadith dha’if are not presented as primary legal sources but rather as supportive material to strengthen or clarify authentic reports. Moreover, the presence of hadith dha’if in his work shows a concrete effort to provide examples of the position and permissibility of using da'if traditions. Thus, people can be wiser in responding to any information, both general and prophetic traditions in the midst of religious life.